2018
DOI: 10.1515/humo-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Estimating maximal heart rate with the ‘220-age’ formula in adolescent female volleyball players: a preliminary study

Abstract: Purpose. Although maximal heart rate (HR max ) is used widely to assess exercise intensity in training, there are limited data with regards to the validity of age-based prediction equations of HR max in volleyball players. Therefore, the aim of the present study was to compare the measured-HR max of two prediction equations (Fox-HR max = 220 − age and Tanaka-HR max = 208 − 0.7 × age) in young female volleyball players. Methods. The study involved 47 volleyball players (age 13.39 ± 2.01 years, body mass 54.0 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…This may not be suitable for predicting HR max of the general population because Fox′s equation was determined based on a review of 10 studies without proper regression analysis and developed in older adults (over 60 years of age) with cardiovascular diseases. Even some studies have demonstrated equation had significantly over and/or underestimated HR max in healthy younger and older adults [ 36 , 37 , 38 ], and our result was also consistent with the previous studies′ outcome by finding overestimating HR max . Although Fox′s equation may seem appropriate for boys and girls aged from 7 to 14 years, the present study suggests that Fox′s equation developed in older adult populations with cardiovascular diseases should be applied with caution to the general population, especially healthy people.…”
Section: Discussionsupporting
confidence: 93%
“…This may not be suitable for predicting HR max of the general population because Fox′s equation was determined based on a review of 10 studies without proper regression analysis and developed in older adults (over 60 years of age) with cardiovascular diseases. Even some studies have demonstrated equation had significantly over and/or underestimated HR max in healthy younger and older adults [ 36 , 37 , 38 ], and our result was also consistent with the previous studies′ outcome by finding overestimating HR max . Although Fox′s equation may seem appropriate for boys and girls aged from 7 to 14 years, the present study suggests that Fox′s equation developed in older adult populations with cardiovascular diseases should be applied with caution to the general population, especially healthy people.…”
Section: Discussionsupporting
confidence: 93%
“…The search resulted in three studies that developed new predictive equations: Mahon et al 12 classified with low methodological quality (50% score), Nikolaidis 23 with moderate quality (68%), and Gelbart et al 14 with high quality (82%). Ten studies performed external validation, of which only one was evaluated with low methodological quality (50%), 24 eight obtained scores between 50 and 70% attaining a moderate quality, [12][13][14][15]23,[25][26][27] and one scored 88%. 28 A single study was carried out to increase values to preexisting equations 29 and was classified as low quality (39%).…”
Section: Resultsmentioning
confidence: 99%
“…From 11 studies, 10 contained nonobese pediatric subjects [12][13][14][15][23][24][25][26][27]29 and 1 contained obese pediatric subjects; 28 of the 10 studies with nonobese sample, 7 included physically active young people. 14,15,23,24,26,27,29 Regarding the criterion to consider the HRmax, 8 of the 11 included studies used the peak HR. [13][14][15]23,26,28,29 Mahon et al 12 measured HRmax as the highest mean value obtained from two consecutive 15 s HR recordings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al igual, que la Universidad Federal de Río de Jainero 17 . En Grecia 18,19 por Hellenic Army Academy; Colombia 20 , con su trabajo colaborativo entre la Universidad Nacional y la Universidad del Bosque, quienes afirman una sobreestimación de dichas fórmulas y que no son predictores adecuados entre sujetos de 18 a 30 años de edad para la FCmáx durante el ejercicio en la altura de Bogotá. Además, de previas investigaciones realizadas por algunos de los autores de este trabajo, concluyen al igual que en este: "No se recomienda las ecuaciones evaluadas por su diferencia significativa respecto a la prueba de esfuerzo máxima; especialmente 220-Edad cuya diferencia de media estuvo por encima de 14 latidos por minutos" 21 .…”
Section: Resultsunclassified